The diurnal variation of mitotic response in the epithelium at the edge of acute ulcers in the rectal mucous membrane of guinea-pigs. - Reeve, D R (1978)
The mitotic response to wounding was examined in ulcers resulting from the excision of small pieces of rectal mucous membrane in two groups of guinea-pigs. One group was wounded at 09.00 hours and a second group at 21.00 hours. Mitotic counts were carried out in the glandular epithelium at the ulcer edges at 2 hourly intervals over a period of 24 hours. Mitotic activity increased in 2--4 hours and thereafter showed a peak-and-trough pattern. The wounded rectal epithelial cells exhibited a diurnal variation with a peak of activity during the day and low activity at night. It would appear that such diurnal rhythmicity is not species-specific because it was similar in both the guinea-pig and rat. The evidence suggests that there is not a chalone-adrenaline complex in the rectal epithelium as the diurnal variation was similar in the nocturnal rat and in the diurnal guinea-pig, and was not abolished by wounding. Mitotic activity was lower in the glands at the immediate wound edge, and in the upper cells of the glands. The cells in these situations are probably designated for migration to close the defect, for migration excludes mitosis. It seems possible that the mechanisms responsible for the circadian rhythm of mitosis are different from those which induce the bursts of mitotic activity after wounding; if so this would be contrary to the chalone concept.